Dengue Hemorrhagic Fever: Past, Present, and Future - Rahmad Budianto; Niniek Budiarti (Fakultas Kedokteran Universitas Lambung Mangkurat, 2019)
Abstract: Dengue viral infection is a global disease with a spectrum of clinical manifestations mild fever to severe disease both dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). DHF is severe form of dengue fever (DF), which can be life-threatening. Climate changes is not the only factor that affects dengue transmission, but also globalization changes includes travel and trade. The pathogenesis of dengue infection is complex. The mechanism involved antibody-dependent enhancement, NS1 and its antibodies, T cells, and DENV genomics. There are several novel methods to detect the presence of dengue virus in the body of infected patients. These include ELISA-specific IgM and IgG detection, detection of monoclonal antibodies and mosquito cell strains, and PCR reverse transcriptase detection. Several trials found novel methods to predict the severity of dengue hemorrhagic fever earlier. These include platelet count, Aspartate aminotransferase / platelet count index (APRI) Index, serum chymase level, serum cytokine/chemokine profile, Tropomyosin-alpha 1 (TPM 1), Reticulocyte Production Index (RPI), and Immature Platelet Fraction (IPF). Several pharmacological therapies are known to have potential antidengue effect. Some of these are corticosteroids, antimalarial drugs, doxycycline and tetracycline, anticholesterol drugs, IVIG, celgosivir, balapiravir, pentoxifylline and calcium supplementation. Some natural products are known to have activity against Aedes aegypti through antiviral mechanisms, larvacidal activity, mosquitocidal, and mosquito repellants. It can be developed as the latest therapy of dengue hemorrhagic fever on the future. The objective of this paper is to provide new insight about the development of dengue hemorrhagic fever related to the history of its distribution, pathogenesis, and the latest developments related to detection methods, severity prediction methods, and the management of dengue hemorrhagic fever on the future. Keywords: globalization changes, novel detection methods, severity prediction methods, latest development in DHF therapy